"It's Okay With Our Culture but We're in a Different Place and We Have to Show Respect": Marshallese Migrants and Exclusive Breastfeeding Initiation. (November 2022) - Ayers, Britni L.; Purvis, Rachel S.; Bogulski, Cari A.; Reece, Sharon; CarlLee, Sheena; Kim Yeary, Karen H.; McElfish, Pearl A.
Background: Pacific Islanders in the United States have lower initiation rates and shorter duration of exclusive breastfeeding compared to other racial/ethnic groups. Research Aim: To describe infant feeding beliefs and experiences of Marshallese living in the United States. Methods: We used a prospective and cross-sectional exploratory, descriptive qualitative design with Marshallese participants ( N = 36) residing in the United States between July 2019 and July 2020. Data were collected at 6–8 weeks postpartum. Our qualitative analytic approach integrated inductive and deductive techniques. Results: Participants' mean age was 27.1 years ( SD = 6.1), and 88.9% ( n = 32) were born in the Marshall Islands. A majority of participants were single, widowed, or in an unmarried partnership ( n = 28, 77.8%). Most participants had a high school education or lower ( n = 30, 83.3%). Mean household size was 7.2 ( SD = 2.8). Fewer than half of participants had no health insurance ( n = 14, 38.9%), and almost all participants (91.7%) did not work at the time of data collection. Two themes emerged: 1) infant feeding initiation and practices; and 2) concerns over breastfeeding in public. The majority of participants' infants received both human milk and formula. Participants described beliefs that breastfeeding in public was against American customs, which influenced their decision about breastfeeding in public. Conclusions: Our study was the first to document infant feeding beliefs and experiences of Marshallese living in the United States at 6–8 weeks postpartum. Findings will inform future health education programs.